Short Course on Industrialized Building System (IBS) - Anon (KUKUM Engineering (Malaysia) Sdn. Bhd., 2011)
Short Course on Industrialized Building System (IBS) was organized by KUKUM Engineering (Malaysia) Sdn. Bhd. in collaboration with Proven IBS Training Centre (M) Sdn. Bhd. and School of Environmental Engineering, Universiti Malaysia Perlis (UniMAP).